2019
DOI: 10.5001/omj.2019.64
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea: Pattern of Use, Patient Adherence, and Safety Profile in Patients with Sickle Cell Disease in Oman

Abstract: Objectives Many barriers contribute to the underutilization of hydroxyurea (HU) in the treatment of sickle cell disease (SCD), and adherence to its use is often reported to be suboptimal. It is important to have information on the safety of HU in patients with SCD. Our study assessed the pattern of use, patients’ adherence to medication, discontinuation of use, and safety of HU in patients with SCD. Methods This cross-sectional study was conducted in the department of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…We adopted the intentional and unintentional medication nonadherence framework in the present study to enhance understanding of unique barriers to hydroxyurea for the SCD population (Hodges et al, 2020). We demonstrated that, even for patients on hydroxyurea, challenges to taking the medicine at the right time and forgetting were crucial unintentional barriers to adherence, consistent with other reports (Badawy et al, 2017;Jose et al, 2019;Hodges et al, 2020). Forgetfulness may be associated with neurocognitive deficits, including memory impairment and diminished executive functioning, that may occur in SCD (Feliu et al, 2011;Prussien et al, 2019;Martin et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…We adopted the intentional and unintentional medication nonadherence framework in the present study to enhance understanding of unique barriers to hydroxyurea for the SCD population (Hodges et al, 2020). We demonstrated that, even for patients on hydroxyurea, challenges to taking the medicine at the right time and forgetting were crucial unintentional barriers to adherence, consistent with other reports (Badawy et al, 2017;Jose et al, 2019;Hodges et al, 2020). Forgetfulness may be associated with neurocognitive deficits, including memory impairment and diminished executive functioning, that may occur in SCD (Feliu et al, 2011;Prussien et al, 2019;Martin et al, 2020).…”
Section: Discussionsupporting
confidence: 79%
“…There are around 3000 cases of SCD in Oman and around 10% of the Omani population are carriers for the sickle cell gene 1. There is no known cure for the disease since it is a genetic disorder except bone marrow transplant 2 3. There are recent studies of gene therapy to cure SCD, those trials are still being investigated 3…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining a refill from the pharmacy and coming for follow-up have been reported as patient-related barriers. Furthermore, a study performed by Jose et al (2019) reported that patients' misperception about HU side effects, poor knowledge on the benefit of HU, and poor health literacy could be the reason for the observed HU underutilization [10].…”
Section: Introductionmentioning
confidence: 99%